Pengaruh komitmen, kepercayaan, dan kepuasan terhadap retensi pelanggan Honda Matic - Naldi Dwi Satriawan; M Nadjib Usman (Journal of Business & Banking, 2018)
This study aimed to determine the effect of commitment, trust, and customer retention both partially and simultaneously. This research is also the development of research with reference to the journals and books for the theoretical framework. The subjet was determined by a purposive sampling, which consisted of 30 respondents as sample determination, and this was added with 59 respondents in order to meet the required sample as based on the theory. The data were collected by distributing questionnaires. This questionnaire is used to determine the degree of the effect of commitment, trust, and satisfaction on the customer retention. The data were analyzed by using a descriptive quantitative. The results show, that trust and customer satisfaction partially have signifi cant effect on customer retention while partial commitment does not affect customer retention. Yet, commitment, trust, and satisfaction simultaneously affect customer retention